Rate Analysis of Intensity Modulated Broadcast Optical Mobile Communication System With User Mobility - Jiajun Gao; Jian Dang; Zaichen Zhang; Liang Wu (IEEE Photonics Journal, 2020)
Optical mobile communication (OMC) provides a hopeful vision to handle with wireless communication scenarios where multiple mobile users are involved. In previous work, achievable rate analysis for broadcast OMC system with coherent transmission and detection is given. Although it was shown that OMC has superior performance compared with conventional schemes, coherent processing imposes strong challenges on the hardware design. In practice, intensity modulation (IM) and direct detection (DD) is more implementation-friendly. However, the result in coherent processing cannot be migrated to IM/DD scenario since IM imposes new constraints on the signal model, making it more challenging to evaluate the rate performance. Motivated by this, in this paper, we investigate the rate performance of broadcast OMC in IM/DD mode with user mobility. The aim of this work is to reveal the potential gain of OMC with IM/DD over some benchmark schemes. By assuming dense pulse amplitude modulation (PAM), the rate is assessed through mutual information with proposed power allocation algorithm. Through simulation results, it is found that OMC outperforms conventional free space optical (FSO) communication in time division mode at high SNR region with not-so-large number of users.